(3GdUahIs - (3RjO Hf Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH , CHh GdMSjf GdYdhqj GdgGTej GdbQTj , hjbGd dg (B((3RjO GdTgjO(B)(3,J (B122 (3g` s
(3ChdgG (B:s
(3MOKfG CHhGdWjH Ydi Hf eMeO s
(3BNQgG (B:s
(3hcd PHjMI cGf GgdgG Cgd edI agi PcjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B190s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B162 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(3977) s
Keywords: (3GdJGQjNs